2018
DOI: 10.1016/j.watres.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Further developing the bacterial growth potential method for ultra-pure drinking water produced by remineralization of reverse osmosis permeate

Abstract: Ensuring the biological stability of drinking water is essential for modern drinking water supply. To understand and manage the biological stability, it is critical that the bacterial growth in drinking water can be measured. Nowadays, advance treatment technologies, such as reverse osmosis (RO), are increasingly applied in drinking water purification where the produced water is characterized by low levels of nutrients and cell counts. The challenge is, therefore, how to measure the low bacterial growth potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
2
7
0
1
Order By: Relevance
“…Expressing the BGP results in the most appropriate way is essential to accurately interpret the test outcome, allowing for achieving the objectives of this study. Currently, the BGP results are expressed either as BGP net for pre-treated (Vital et al, 2010;Park et al, 2016) and non-pre-treated (i.e., direct incubation) (Prest et al, 2016a;Nescerecka et al, 2018) samples, or as BGP max (Joret et al, 1991;Percherancier et al, 1996;Sousi et al, 2018). The results of the present study suggest that BGP max gives a better representation of the BGP of water, since the effect of initial cell count is ruled out (Figure 2).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Expressing the BGP results in the most appropriate way is essential to accurately interpret the test outcome, allowing for achieving the objectives of this study. Currently, the BGP results are expressed either as BGP net for pre-treated (Vital et al, 2010;Park et al, 2016) and non-pre-treated (i.e., direct incubation) (Prest et al, 2016a;Nescerecka et al, 2018) samples, or as BGP max (Joret et al, 1991;Percherancier et al, 1996;Sousi et al, 2018). The results of the present study suggest that BGP max gives a better representation of the BGP of water, since the effect of initial cell count is ruled out (Figure 2).…”
Section: Discussionmentioning
confidence: 67%
“…Reverse osmosis (RO) filtration is capable of producing drinking water with ultra-low nutrient level, and thus, very low bacterial growth potential (BGP) (Park and Hu, 2010;Dixon et al, 2012). However, Sousi et al (2018) demonstrated that the existing BGP bioassays are not suitable for ultra-low nutrient water, such as remineralized RO permeate (BGP = 50-100 × 10 3 cells/mL), because of their high detection limit. Additionally, more care should be taken when measuring the BGP of ultra-low nutrient water samples due to the high susceptibility of this water type to sample preparation procedures that can introduce contamination (i.e., BGP increase).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations